Tinjauan Qira'ah Mubadalah Faqihuddin Abdul Kodir Dan Maqashid Syariah Dalam Pemenuhan Hak Anak Pasca Perceraian - Dede Al Mustaqim; Nazula Alfirahmah (Institut Agama Islam Negeri Metro, 2025)
Abstract: This study aims to examine the practice of fulfilling children's rights after divorce in Kerandon Village, Talun District, Cirebon Regency, through the perspectives of Qira’ah Mubadalah by Faqihuddin Abdul Kodir and Maqashid Sharia. The research focuses on three main questions: (1) how children's rights are fulfilled at the local level following a divorce, (2) how the values of reciprocity (mubadalah) are applied in post-divorce parental relationships, and (3) how the principles of maqashid sharia are reflected in the fulfillment of children’s rights. This study uses a descriptive qualitative method with a normative-sociological approach. Data were collected through interviews with five divorced families with children, as well as through observation and document study. Data analysis follows the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the fulfillment of children's rights after divorce is significantly influenced by social, economic, and relational factors between the parents. In some cases, the principles of Qira’ah Mubadalah, such as mutual consultation (musyawarah) and consent (taradhin), are internalized through productive and collaborative communication between parents. However, there are also instances where the failure to fulfill children’s rights stems from broken communication and the negligence of one parent. From the maqashid sharia perspective, some families continue to uphold the principles of protecting religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal) of the child, albeit under limitations. This study highlights the importance of a reciprocity-based and maqashid-oriented approach in designing post-divorce child protection policies and practices. Keywords: Qira’ah Mubadalah, Maqashid Sharia, Children's Rights, Divorce